Evaluating a Learning Object Repository: A Pilot Study - Caws, Catherine (IALLT Journal of Language Learning Technologies, 2005)
This article describes a pilot study performed in the Fall of2004 in order to evaluate the functional aspect of FLORE, a new learning object repository for French teaching and learning. The study seeks to elaborate a standard and iterative evaluation process in order to better analyse the educational value of learning object repositories. Developped as a prototype, FLORE is a web portal similar to MERLOT or CAREO that aggregates a collection of objects and sites for the community of educators and learners of the French language. The author here describes its specificities and draws initial conclusions based on the participants’ evaluations and contributions towards the further development of the repository.